Strategi Paikem Dalam Pembelajaran Pendidikan Agama Katolik - Sergius Lay; Atanasius Arianto Halawa; Paulinus Kanisius Ndoa (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2024)
Based on the learning process which is often monotonous and boring in classrooms between teachers and students, this research seeks to understand and implement the concept of Active, Innovative, Creative, Effective and Fun learning and Catholic Religious Education Learning Activities, as well as offering it to students. PAK teachers to carry out reforms in PAK learning strategies and methods. The method used in this research is a literature study approach or qualitative method. The results of this research are: there are still many PAK teachers who teach using conventional learning methods, the PAIKEM learning strategy is one strategy that can make the classroom atmosphere better in learning and can improve the quality of PAK learning, every PAK teacher is needed to learn various PAK learning models, strategies and techniques to improve the quality of learning and a new understanding that students are the center of learning activities in PAK.